2014
DOI: 10.1097/scs.0000000000000847
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Age Estimation by Spheno-Occipital Synchondrosis Fusion Degree

Abstract: The analysis of ossification points plays a considerable role in forensic age estimation. Although traditional methods are still in use, researchers are working on different age estimation procedures especially within the development of radiologic methods. One of these methods is to define spheno-occipital synchondrosis fusion degree. Spheno-occipital synchondrosis, an important growth point on cranial base, provides noteworthy information about age estimation through its late stage ossification nature. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 0 publications
5
59
1
8
Order By: Relevance
“…However, it is worth mentioning that the youngest and oldest ages are affected by sample compositions and age limits. Some studies have samples that include individual ages up to 25 years, and they reported Stage 3 closure age in both sexes around 20 years and above [ 18 , 30 ]. The same could be said when we calculate the mean age of oldest individuals with completely open SOS (Stage 0).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is worth mentioning that the youngest and oldest ages are affected by sample compositions and age limits. Some studies have samples that include individual ages up to 25 years, and they reported Stage 3 closure age in both sexes around 20 years and above [ 18 , 30 ]. The same could be said when we calculate the mean age of oldest individuals with completely open SOS (Stage 0).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies assert complete closure between 17 and 25 years in males and females [ 8 , 11 ]. Later, differences in closure age between males and females were reported with females beginning to fuse between 11 and 14 years and males between 13 and 16 years [ 12 18 ]. More recently, Computed Tomography (CT) and Cone Beam Computed Tomography (CBCT) have been used in SOS evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spheno-occipital synchondrosis has gained importance for both age estimation and clinical applications, particularly because of its late ossification process [ 32 ]. Fusion of the spheno-occipital synchondrosis usually starts about 2 years earlier in females than in males [ 11 , 33 ], in a similar way than that observed during general growth at the beginning of puberty [ 34 ]; however, no significant differences seem to occur at the end of the process [ 12 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age estimation of subjects by using the closure stage of spheno-occipital synchondrosis is widely variable among studies, which may be attributed to the different methodological approaches used, i.e. macroscopic [ 11 , 35 , 36 ], radiographic [ 37 ] or CBCT [ 12 14 , 32 ], different scoring systems, sex, or population variations.…”
Section: Discussionmentioning
confidence: 99%